1969
DOI: 10.1002/ange.19690810204
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalente Moleküle

Abstract: Salzlosung befordern [104.1061.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(37 citation statements)
references
References 59 publications
2
33
0
2
Order By: Relevance
“…The lead atoms of 3 a and 3 b are coordinated by two THF and pyridine molecules, respectively, from above and below the plumbole rings, and the O À Pb À O and N À Pb À N angles are 175.62(6)8 and 168.41 (7)8, respectively, which are wider than the corresponding angles in Jacobs (A: 157.7(1) and 158.6(1)8) [20a] and Jurkschats (B: 149.5(1)8) [20b] compounds (Figure 3), thus suggesting that each compound has a hypervalent 10-Pb-4 structure. The PbÀO distances in 3 a are 2.6606(19) and 2.6635 (19) , which are similar to those of Joness C and Roeskys D hypervalent Pb II compounds, [20g, h] but longer than those found in Jurkschats B and Lyczkos E related compounds. [20b,f] The Pb À N distance in 3 b is 2.6877 (17) , which is similar to those of Jacobs hypervalent Pb II compounds.…”
Section: Resultsmentioning
confidence: 79%
“…The lead atoms of 3 a and 3 b are coordinated by two THF and pyridine molecules, respectively, from above and below the plumbole rings, and the O À Pb À O and N À Pb À N angles are 175.62(6)8 and 168.41 (7)8, respectively, which are wider than the corresponding angles in Jacobs (A: 157.7(1) and 158.6(1)8) [20a] and Jurkschats (B: 149.5(1)8) [20b] compounds (Figure 3), thus suggesting that each compound has a hypervalent 10-Pb-4 structure. The PbÀO distances in 3 a are 2.6606(19) and 2.6635 (19) , which are similar to those of Joness C and Roeskys D hypervalent Pb II compounds, [20g, h] but longer than those found in Jurkschats B and Lyczkos E related compounds. [20b,f] The Pb À N distance in 3 b is 2.6877 (17) , which is similar to those of Jacobs hypervalent Pb II compounds.…”
Section: Resultsmentioning
confidence: 79%
“…Encouraged by these results we have investigated the reactions of Ar 2 TeO with 2-, 3-and 4-pyridine carboxylic acids (LH). We have been able to isolate Ar 2 Te(L)(OH) (1), Ar 2 Te(L) 2 (2), Ar 2 Te(L)OTe(L)Ar 2 (3) and Ar 2 Te(L)OTe(Ar) 2 OTe(L)Ar 2 (4). The synthesis, reactivity and structural characterization of these divergent product types is discussed herein.…”
Section: Introductionmentioning
confidence: 95%
“…We were interested in investigating the corresponding reactions with organotellurium oxides to find out if divergent structural types can be formed by modulating the nature of protic acid. As part of this research activity we have recently reported the reactions of Ar 2 TeCl 2 (Ar = 4-MeO-C 6 H 4 ) with 1,1 0 -ferrocenedicarboxylic acid (L 0 H 2 ) which afforded the heterometallic macrocycle [Ar 2 TeL 0 ] 2 . [42].…”
Section: Introductionmentioning
confidence: 99%
“…Calculations are also reported for the staggered conformations of the protonation products CH3SH,+ and CH3PH3+. Thevariousgeometriesandtotalenergies of the two heavy-atom sulfur and phosphorus lThe usual equation [3], which approximates the solution to Dl, [3] Ae, = 2(A,, -eioSij)2i(eio -ero) could not be used because of the unusually large stabilizing interactions in these molecules. Can Tables 1 and 2, respectively.…”
mentioning
confidence: 99%